English Teachers’ Perception in Teaching Listening - Episiasi Episiasi; Januarius Mujiyanto; Suwandi Suwandi; Rudi Hartono (International Conference on Science, Education, and Technology, 2021)
This study is aimed to investigate the English teachers’ perception in teaching listening. The English teachers have a different style of teaching. In teaching, the teachers should use three steps of teaching, they are pre-teaching, while-teaching, and closing. The case study was conducted on the seven English teachers of STKIP PGRI Lubuklinggau, South Sumatera province, Indonesia. The questionnaire and interview were used by the researcher for collecting the data. The result of the study showed that they found challenging in teaching listening. The quality of the teaching and learning process should be the important thing because it can achieve the goal of teaching and improve the student’s listening comprehension mastery.